Fatty acid compositions of silver catfish, pangasius sp. farmed in several rivers of Pahang, Malaysia - Hashim, Ridzwan; Jamil, Elyna Fatinie; Zulkipli, Farah Hanis; Mohd Daud, Jamaluddin (Japan Oil Chemists' Society, 2015)
Pangasius micronemus (Black Pangasius sp.) and Pangasius nasutus (Fruit Pangasius sp.) are two species of silver catfish widely consumed in Malaysia. The present study evaluated fatty acid profiles of fish muscles in these two Pangasius sp. from different farms and locations to determine which species or location is better in term of lipid quality. The results showed MUFAs (monounsaturated fatty acids) content was highest (35.0-44.4% followed by SFA (saturated fatty acid) [32.0-41.5%] and PUFAs (polyunsaturated fatty acids) [9.3-19.3%]. P. micronemus of Sg. Kanchong displayed higher palmitic acid (SFA; 29.0%) than P. nasutus from Peramu (23.5%). In contrast, oleic acid (MUFA) revealed highest in . nasutus from P. nasutus (38.1%) while lowest in P. micronemus of Sg. Kanchong (19.3%) and lower most in P. nasutus from Peremu (9.3%). P. micronemus presented with a higher EPA (eicosapentaenoic acid) [1.0-1.4%], DHA (docosahexaenoic acid)[1.7-2.8%] and LA (linoleic acid) [11.8-12.0%] than P.nasutus (EPA; 0.3%, DHA; 1.0% LA; 4.8%). However, P. nasutus established higher GLA (gamma-linolenic acid) [0.4%] than P. micronemus (0.04-0.06%). Both Pangasius sp. can be regarded as good supplies of omega-3 and omega-6. Overall, P. micronemus from Sg. Kanchong is the best choice among all for reason high in EPA and DHA.